1993
DOI: 10.1152/ajpheart.1993.265.5.h1471
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of adenosine-mediated coronary vasodilation exacerbates myocardial ischemia during exercise

Abstract: Persisting coronary vasoconstrictor tone that is responsive to exogenous adenosine administration has been demonstrated during myocardial ischemia. Therefore, the role and extent of endogenous adenosine-mediated coronary vasodilation in opposing coronary vasoconstriction within regions of ischemic myocardium was investigated in 10 chronically instrumented exercising dogs. Studies were performed on dogs with left circumflex coronary artery stenosis during treadmill exercise (6.5 km/h, 6% grade), while myocardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 0 publications
1
36
0
1
Order By: Relevance
“…Gallagher et al (37) demonstrated that full wall thickening depends on subendocardial perfusion and correlates poorly with subepicardial perfusion, suggesting that the decreases in blood flow produced by glibenclamide and 8-phenyltheophylline in the present study, which were paralleled by decreases in systolic wall thickening, were also present in the innermost layers. This is also supported by our previous studies that demonstrated that adenosine receptor blockade aggravates hypoperfusion in all myocardial layers distal to a coronary artery stenosis during exercise (4,5). The observation in the present study that, after K ϩ ATP channel blockade with glibenclamide, systolic wall thickening was depressed proportionally more than coronary artery blood flow could be interpreted to suggest that a nonuniform blood flow distribution could have occurred with a more prominent decrease in subendocardial than in subepicardial blood flow.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Gallagher et al (37) demonstrated that full wall thickening depends on subendocardial perfusion and correlates poorly with subepicardial perfusion, suggesting that the decreases in blood flow produced by glibenclamide and 8-phenyltheophylline in the present study, which were paralleled by decreases in systolic wall thickening, were also present in the innermost layers. This is also supported by our previous studies that demonstrated that adenosine receptor blockade aggravates hypoperfusion in all myocardial layers distal to a coronary artery stenosis during exercise (4,5). The observation in the present study that, after K ϩ ATP channel blockade with glibenclamide, systolic wall thickening was depressed proportionally more than coronary artery blood flow could be interpreted to suggest that a nonuniform blood flow distribution could have occurred with a more prominent decrease in subendocardial than in subepicardial blood flow.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, when coronary pressure was reduced, adenosine blockade significantly decreased blood flow during exercise. Similarly, adenosine receptor blockade has been previously reported to decrease coronary blood flow distal to a coronary artery stenosis (4,5). These findings suggest that reductions of coronary artery pressure sufficient to cause myocardial hypoperfusion result in augmented adenosine production, which contributes to coronary vasodilation.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Adenosine is an important metabolite involved in vasodilation, and is released from various tissues as an endogenous protective agent in ischemia (41 -43). It has been reported that endogenous adenosine contributes significantly to coronary vasodilation during ischemia (44). ATP-sensitive K + channel activation may play an important role in adenosine-induced vasodilation (42,45).…”
Section: +mentioning
confidence: 99%